'Shh … quiet! Here they come.' Black employees as targets of office gossip. Issue 2 (29th April 2016) - Carrim, Nasima M. H.
Abstract : This study explored black employees' experiences of racial profiling by their white peers through the medium of gossip at a historically white, South African university. Participants consisted of 24 black employees (males = 50%, females = 50%; support staff = 50%, academic staff = 50%). The employees completed a semi-structured interview that elicited their perceptions of the settings in which gossip about black employees occurred, the perceived intentions of such gossip, and their responses to it. The data obtained was thematically analysed. Findings suggested that the gossip targeted black employees who were absent from meetings, and that such gossip undermined the work performance and morale of these employees.